Market Response to European Regulation of Business Combinations - Aktas, Nihat; de Bodt, Eric; Roll, Richard (Journal of Financial and Quantitative Analysis, 2004)
Abstract Acquisitions, mergers, and other business agreements face increasing regulatory scrutiny, even when they involve firms domiciled outside the territory of regulatory authorities. Recent examples include mergers between American firms that were approved by American regulators but blocked by European regulators. Regulatory reciprocity seems a likely future trend. There are obvious consequences for the successful completion of future business combinations. This paper explains the regulatory procedures of the European Commission with respect to business combinations, documents the price reactions of subject firms on dates from the initial announcement to the final regulatory decision, and studies whether European regulators tend to shield European firms from foreign competition. Our main results are: i) the market clearly reacts to European regulatory intervention even when the subject firms are non-European, ii) the probability of intervention is not related to the nationality of the bidder, however, iii) when intervention does occur, the market anticipates it will be more costly when the bidder is non-European, so protectionism cannot be rejected outright, and iv) regulatory interventions are anticipated by investors, so they affect the initial announcement returns.